Determinant Factors on Indonesia Economic Growth - Revan Adityara (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2019)
Indonesia's economic growth has not been able to become an accelerator of efforts to overcome unemployment and poverty. Indonesia's economic growth is still too small even since 2011-2015 tends to experience a significant decline. Analysis of the factors that influence economic growth can be approached through two sides, namely from the supply side (supply-side economics) and the demand side (demand-side economics). This research was conducted with two approaches, namely from the supply side, by looking at the impact of capital accumulation. The data analysis method used in this research is multiple linear regression using the Ordinary Least Square (OLS) model, which was previously performed first using the classic assumption test to ensure that the model used meets normality assumptions and does not contain multicollinearity, heteroscedasticity, and serial correlation so meet the Best Linear Unbiase Estimate (BLUE) assumption.. This finding is in line with economic theory, both based on the aggregate supply side, and the aggregate demand side